Phylogeographic Analysis Suggests a Recent Population Bottleneck in the Rare Red Sea Tridacna squamosina - Lim, Kah Kheng; Rossbach, Susann; Geraldi, Nathan R.; Serrão, Ester A.; Duarte, Carlos M. (Frontiers in Marine Science, 2021)
Giant clams are an important ecological component of coral reefs in the Red Sea, as they enhance the reef’s productivity and provide habitat that can increase diversity. Three species of giant clams, namely Tridacna maxima, T. squamosa and T. squamosina have been described within the Red Sea. However, due to its scarcity, information about the distribution and ecology of T. squamosina in the Saudi Arabian Red Sea is still lacking. This study used DNA barcoding to confirm the identity of the rare T. squamosina in the Farasan Banks. Six mtCOI fragments (500 bp) of T. squamosina were successfully amplified using the SQUA-primers for the first time. We used our data along with 18 reference sequences (16S) from online database to assess the genetic diversity and population structure of T. squamosina. Low genetic diversity among the T. squamosina populations inferred from the 16S sequences implies a recent bottleneck for this species, which is supported by their historically higher diversity based on the coalescent-based estimator. Given the small population abundance and limited genetic variation of T. squamosina, it may warrant immediate local protections such as biobanking and fertility preservation programs as well as effective integrated coastal zone management plans.